Pengalaman hidup pasien dengan stoma: A scoping review - Maryati, Ida; Sarjono, Kalih; Miladi, Qonita Nur; Widaningsih, Ida; Saritesa, Nining; Ermaya, Asep; Anggraeni, Rina (Holistik Jurnal Kesehatan, 2025)
Background: The lived experience of patients with a stoma is an important aspect that is often overlooked in health care. Patients with a stoma often face physical and emotional challenges that can affect their quality of life. The changes experienced after stoma surgery can lead to feelings of loss of control and challenges of adaptation. In addition, social support and education from health care providers play a significant role in helping patients adjust. Purpose: To identify patients' lived experiences with a stoma. Method: Scoping review using three databases, namely CINAHL, PubMed, and Scopus with the keywords of patient life experience with stoma, social support, and stoma adaptation. The initial articles found were 679, then 11 articles were included in the study. Results: Patients with stomas have difficulty adapting, but good social support and education from nurses can help improve a sense of control and quality of life. Appropriate interventions can help reduce anxiety and improve the patient's quality of life. Conclusion: The importance of ongoing psychosocial support and education by nurses to help patients manage physical and emotional changes. Suggestion: Further research is recommended to further explore the effectiveness of educational interventions and long-term social support in patients with stoma.   Keywords: Experiences; Patients; Stoma.   Pendahuluan: Pengalaman hidup pasien dengan stoma merupakan aspek penting yang sering diabaikan dalam perawatan kesehatan. Pasien dengan stoma sering menghadapi tantangan fisik dan emosional yang dapat memengaruhi kualitas hidup mereka. Perubahan yang dialami setelah operasi stoma dapat menyebabkan perasaan kehilangan kendali dan tantangan adaptasi. Selain itu, dukungan sosial dan edukasi dari tenaga kesehatan berperan signifikan dalam membantu pasien menyesuaikan diri. Tujuan: Untuk mengidentifikasi pengalaman hidup pasien dengan stoma. Metode: Scoping review menggunakan tiga database yaitu CINAHL, PubMed, dan Scopus dengan kata kunci pengalaman hidup pasien dengan stoma, dukungan sosial, dan adaptasi stoma. Artikel awal yang ditemukan adalah sebanyak 679, kemudian 11 artikel disertakan dalam penelitian. Hasil: Pasien dengan stoma mengalami kesulitan dalam beradaptasi, namun dukungan sosial yang baik dan edukasi dari perawat dapat membantu meningkatkan rasa kontrol dan kualitas hidup. Intervensi yang tepat dapat membantu mengurangi rasa cemas dan meningkatkan kualitas hidup pasien. Simpulan: Pentingnya dukungan psikososial dan edukasi berkelanjutan oleh perawat untuk membantu pasien mengelola perubahan fisik dan emosional. Saran: Penelitian selanjutnya disarankan untuk mengeksplorasi lebih lanjut tentang efektivitas intervensi edukatif dan dukungan sosial dalam jangka panjang pada pasien dengan stoma.   Kata Kunci: Pasien; Pengalaman; Stoma.